Intraocular production of a cytokine (CINC) responsible for neutrophil infiltration in endotoxin induced uveitis. Issue 7 (July 1996) - Guex-Crosier, Y.; Wittwer, A. J.; Roberge, F. G.
Abstract : AIMS/BACKGROUND: The subcutaneous injection of bacterial endotoxin in Lewis rats produces an acute intraocular inflammation evolving over a 24 hour period. This endotoxin induced uveitis (EIU) is characterised by a biphasic protein exudation and a cellular infiltrate composed of macrophages and polymorphonuclear neutrophils (PMNs). This model was used to study the mechanism of cellular infiltration in ocular inflammation. METHODS: EIU was induced by a subcutaneous injection of lipopolysaccharide (LPS) (S typhimurium) at 350 micrograms/kg. The levels of cytokine induced neutrophil chemoattractant (CINC) were measured every 2 hours in the serum and in the aqueous humour by ELISA. The intraocular inflammation was quantified by protein measurement and leucocyte counting. RESULTS: The kinetics of CINC production in the systemic circulation showed a rapid rise, peaking 2 hours after LPS injection, followed by a progressive decline over the next 8 hours. In the eye, the CINC levels increased above the serum levels 10 hours after EIU induction corresponding to the time of cellular infiltration. When leucocyte entry in the eye was inhibited by 56% and 64% with an antiadhesion molecule antibody, there was only a slight reduction in the aqueous humour CINC levels of 9% and 16%, respectively, indicating that CINC was produced by ocular tissue cells. The specific effect of CINC in the eye was confirmed when a direct intraocular injection of 250 ng of purified CINC was followed by significant PMN infiltration, in the absence of protein exudation. CONCLUSION: The data indicate that the production of the CINC chemotactic factor by ocular tissue participates in the inflammatory reaction in EIU.